Neighbourhood identity versus city identity: An inter-scalar perspective via urban layers in a historical zone under transformation - Edmond Manahasa; Artea Zera; Odeta Manahasa; Artan Hysa (Frontiers of Architectural Research)
Post-socialist urban development in the Albanian capital, Tirana, is characterized by unplanned urbanization that led to the loss of the city's historical fabric. This study focuses on a historic neighbourhood of Tirana affected by urban transformation. It defines housing as the predominant function that has influenced the morphology of the neighbourhood and divides it into three layers, namely pre-socialist, socialist, and post-socialist.The aim is to reveal the influence of each urban layer on neighbourhood and city identity. To achieve this goal, we rely on the concept of place identity, which consists of physical elements and identificatory relations. The methodology includes sampling of citizens (67 per layer), surveying (No = 201), GIS-mapping and data analysis by clustering physical elements (landmark, house, street, public space) and identificatory relation features (memories, experiences, social and self-identity aspects).The results show that the city identity is reported to be slightly higher compared to the neighbourhood identity. The residents of older layers compared with those of newer have higher identification with both neighbourhood and city. Finally, the neighbourhood identity is generated by houses, as physical aspects, and socialization as identificatory relation, whereas city identity is generated by public spaces, as physical aspects, and as identificatory relation aspects socialization, and self-identity aspects.